2022
DOI: 10.1038/s41598-022-06666-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial epibiotic community of the deep-sea galatheid squat lobster Munidopsis alvisca

Abstract: Life at hydrothermal vent sites is based on chemosynthetic primary producers that supply heterotrophic microorganisms with substrates and generate biomass for higher trophic levels. Often, chemoautotrophs associate with the hydrothermal vent megafauna. To investigate attached bacterial and archaeal communities on deep-sea squat lobsters, we collected ten specimens from a hydrothermal vent in the Guaymas Basin (Gulf of California). All animals were identified as Munidopsis alvisca via morphological and molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…Community analysis based on RNA sequences showed a similar trend ( Table 1 ), although DNA-derived communities were generally less diverse and less even than RNA-derived communities. The dissimilarity between DNA and RNA supports the hypothesis that RNA is probably more indicative of active members of investigated communities and underlines that stand-alone 16S rRNA gene results should be interpreted cautiously ( 20 ). Nevertheless, the DNA and RNA-derived microbial communities overlapped; of the abundant OTUs, none was found exclusively in either the DNA or RNA data set, indicating that the abundant bacteria constitute active members of the communities ( Table 3 ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Community analysis based on RNA sequences showed a similar trend ( Table 1 ), although DNA-derived communities were generally less diverse and less even than RNA-derived communities. The dissimilarity between DNA and RNA supports the hypothesis that RNA is probably more indicative of active members of investigated communities and underlines that stand-alone 16S rRNA gene results should be interpreted cautiously ( 20 ). Nevertheless, the DNA and RNA-derived microbial communities overlapped; of the abundant OTUs, none was found exclusively in either the DNA or RNA data set, indicating that the abundant bacteria constitute active members of the communities ( Table 3 ).…”
Section: Discussionsupporting
confidence: 73%
“…Such shifts in diversity may happen due to apparent environmental stresses as we have shown earlier ( 17 ). Leinberger et al ( 20 ), who studied the epibacterial community of the deep-sea galatheid Munidopsis alvisca , did not observe lesions or other morphological changes in the carapace that would indicate carapace disease in any of these animals from 2000 m depth. However, shell disease might be a normal phenomenon in crustaceans, possibly occurring also without anthropogenic influences or impacts of climate change ( 43 ).…”
Section: Discussionmentioning
confidence: 97%
“…(Fukunaga et al, 2006;Perez-Pascual et al, 2017). The general consensus is that Flavobacteriia subsist on abundant organic matter in the epipelagic zone, which may explain why deep-sea HV systems usually show no or very low proportions of Flavobacteriia-related bacteria in contrast to the shallow-water HV system of Kueishan Island (Goffredi, 2010;Salazar et al, 2016;Cerqueira et al, 2017;Leinberger et al, 2022). Nevertheless, Flavobacteriia were not abundant in other shallowwater HV systems (Rajasabapathy et al, 2018).…”
Section: Biochemical Processes Of Symbiotic Bacteria Species In Hv Crabsmentioning
confidence: 99%
“…Indeed, a previous study showed that the microbial community on the carapace of fiddler crabs (Uca panacea) was closely related to the community in the surrounding sediments (Cuellar-Gempeler and Leibold, 2019). Furthermore, the microbial epibiotic communities' significance on the carapaces of deep-sea galatheid squat lobsters (Munidopsis alvisca) was interpreted as a mutualistic host-microbe relationship for sulfide detoxification (Leinberger et al, 2022). Up to now, only two studies have probed X. testudinatus tissues to examine the importance and potential contributions of symbiosisassociated bacteria (Ho et al, 2015;Yang et al, 2016); both studies showed diverse bacterial constitutions in different tissues of X. testudinatus.…”
Section: Introductionmentioning
confidence: 99%
“…Specific symbiotic bacteria have been identified as critical to marine animals, for example to protect shrimp larvae from fungal infections (Gil-Turnes et al, 1989), provide nutrition and secondary molecules for defense in isopods (Lindquist et al, 2005), or to form the intricate connections between sponges and their microbiota (Pita et al, 2018). In deep sea squat lobsters, Munidopsis alvisca , bacteria and archaea on the shells of lobsters living near hydrothermal vents helped process potentially detrimental chemicals and may support the health of shells (Leinberger et al, 2022). While many of the bacteria in that study were novel and could not be identified, there were some found by Leinberger et al that were also isolated in this study.…”
Section: Discussionmentioning
confidence: 99%